Manajemen Sumber Daya Manusia dalam Pengelolaan Budidaya Ikan Lele CV Tropika Farm - Simangunsong, Bonse Aris Mandala Putra; Hikmawatty , Sitti; Budiman, Dana; Pratiwi, Intan Deanida; Gunawan, Iwan; Maris, Salix Fini (JUDICIOUS, 2025)
This study discusses the important role of human resource management (HRM) in catfish farming at CV Tropika Farm. The research shows that effective management can improve efficiency and productivity in catfish farming. Innovative solutions in water, climate management and feed management also have significant positive impacts. The findings are expected to be the basis for further development in improving the sustainability of catfish farming in the future. HRM in catfish farming includes aspects of water management, fertilization, feeding and climate management. Adaptation strategies to deal with climate challenges in catfish breeding include selection of seeds that are resistant to climate change, regulation of pond temperature, water quality management, and utilization of alternative water sources. The research was conducted using a qualitative method, using primary data from interviews with CV Tropika Farm employees and secondary taken from literature, journals and data from CV Tropika Farm, Batununggal, Cibadak District, Sukabumi Regency. Good HR management can have a positive impact on overcoming problems faced and reducing risks that can affect catfish hatchery operations.